Sistema de rastreabilidade do transtorno do déficit de atenção e hiperatividade - SOUTDAH - Moreira, Andrea Rodrigues (2024)
Mental disorders, such as Attention Deficit Hyperactivity Disorder (ADHD), present significant global challenges, particularly exacerbated in Brazil, where approximately 40% of students in the early grades face educational difficulties related to this disorder, worsened by the COVID-19 pandemic. 19. This study proposes an innovative solution capable of tracking and characterizing behaviors associated with ADHD in individuals. Software, based on recommendations from scientific literature that uses the SNAP-IV method, allows the description and scoring of 18 ADHD symptoms on a scale of five levels of severity, which associates the symptomatic manifestations of ADHD and contributes to adequate intervention. After applying the instrument to a sample of 532 participants from high school and higher education, it was found that 9.02% individuals reported having a previous or current diagnosis of ADHD, of which 81.25% reported using medication for the disorder. The "No Self-Reference" category (44.92%) indicates a possible lack of awareness or reluctance to recognize the symptoms of the disorder. The exploratory factor analysis of SNAP IV revealed the consistency of a measure composed of eighteen items, grouped into two factors, with satisfactory indicators of consistency and factorability. Furthermore, significant differences were identified between groups with and without a history of ADHD diagnosis, demonstrating the measure's ability to distinguish between these groups based on the individuals' own reports. Regarding qualitative results, the analysis revealed a diversity of symptoms and perceptions associated with ADHD, highlighting the importance of a holistic approach in diagnosing and treating the disorder. In this research we conclude that SOUTDAH makes a significant contribution to mental health by offering an innovative approach to ADHD and we recognize the need for continuous improvement and integration with other clinical practices.